Integration of Local Wisdom in Mathematics Learning: Systematic Literature Review - Magdalena Dhema; Mohammad Fitri; Maria Aprilia Venerani Gokun (Journal of Teaching and Learning Mathematics, 2026)
The integration of local wisdom in mathematics learning is gaining increasing attention as it helps bridge abstract mathematical concepts with students’ contextual experiences. Learning that incorporates local cultural values, practices, and artifacts not only enhances conceptual understanding but also strengthens cultural identity and the relevance of learning in everyday life. However, existing studies on this topic remain scattered, with diverse approaches, findings, and levels of effectiveness. Therefore, a systematic literature review is needed to identify research trends, implementation forms, and the impacts of integrating local wisdom in mathematics learning. This study aims to systematically analyze the integration of local wisdom in mathematics learning using a Systematic Literature Review (SLR) combined with bibliometric analysis. The data were obtained from the Scopus database, covering publications from 2019 to 2026 using the keyword "local wisdom in mathematics learning." Following the PRISMA framework, a total of 37 relevant articles were selected for analysis. The findings reveal that research on local wisdom in mathematics learning remains relatively limited but has shown a fluctuating increasing trend in recent years. The distribution of studies is dominated by Indonesia, which also serves as the central hub for global research collaboration in this field. Thematically, the studies primarily focus on the integration of local wisdom through ethnomathematics, traditional games, and contextual learning approaches. Furthermore, the integration of local wisdom has been shown to enhance students' conceptual understanding, learning motivation, engagement, and higher-order thinking skills. However, several challenges remain, including limited teacher readiness, lack of contextual learning resources, and uneven research distribution. Therefore, future studies should focus on underexplored regions and strengthen the design of culturally responsive and sustainable mathematics learning models.